The Effectiveness of Cognitive Restructuring Technique Cbt Group Counseling to Reduce the Fear of Missing Out and Improve Interpersonal Communication in Students - Hernanda Rizky Rachmawati (Asesment : Journal Of Counseling Guidance, 2026)
Background : In the digital era, excessive social media use among adolescents has contributed to the emergence of Fear of Missing Out (FoMO), which can negatively affect interpersonal communication. This issue highlights the need for effective counseling interventions to help students manage FoMO and improve social interaction. Objectives : To examine the effectiveness of Cognitive Behavior Therapy (CBT) group counseling with cognitive restructuring techniques in reducing FoMO and improving interpersonal communication among students. Method : This study used a quantitative experimental design with a randomized pretest-posttest control group. Sixteen grade XI students of SMK Bina Patria 1 Sukoharjo, selected based on high FoMO and low interpersonal communication, were divided into experimental and control groups. The experimental group received six CBT group counseling sessions using cognitive restructuring techniques, while the control group participated in conventional group discussions. Data were collected using the FoMO Scale and Interpersonal Communication Scale and analyzed using MANCOVA and Wilcoxon tests. Finding and Implication : The intervention significantly reduced FoMO and improved interpersonal communication among students (p < 0.01). The findings indicate that cognitive restructuring helps students challenge irrational thoughts related to social media and develop healthier communication behaviors. This approach can be applied by school counselors as an effective intervention for addressing digital-era psychological and social challenges. Conclusion : CBT group counseling with cognitive restructuring techniques is effective in reducing FoMO and enhancing students’ interpersonal communication skills.